Knowledge Attitude and Practice about Obesity and Its Complication in Rural Area of Lahore - Anwar, Asma; Hussain, Muhammad; Sarwar, Hajra; Afzal, Muhammad; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Introduction: The population has not been investigated extensively about understanding and perception about obesity and its complications. The aim of the study was to investigate the understanding, recognition and practice between overall population in the selected areas of Lahore related to obesity and its complications. Methods: The descriptive study which involved 100 respondents. The respondents from Hussain Abad Lahore were conveniently approached and recruited. A pre-approved, questionnaire was used for data accumulation. SPSS version 20 was used both descriptive and inferential statistics. Results: From Out of the total 100 participants, 53% were females and 47% were males. Almost the half Participant 45% was in the age of 35years. Nearly 91% respondents don’t have idea about normal body mass index of adults. While 89% participants don’t know hormonal problems can lead the obesity. However 51% participants know that obesity can lead the heart problems. . Just about 52% participants were agreeing that when the person consumes extra calories than the individual burns obesity can occurs. 44% participants were agreed that psychological factors can influence the eating habits and obesity more over 36% are agreed that junk food takers are more susceptible to obesity. Only 3% participant checks their Body Mass Index (BMI) level. 26% change their eating habits, physical activity in order to maintain their physique and 11% takes of junk food. Conclusion: The respondents were more careful that obesity happens when a man expends a bigger number of calories than a man devours it. However the respondents know about obesity and its entanglements to some degree, their preparation towards weight isn't general which ought to be investigated later on for better human administrations, and prosperity comes about. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 187-191